Potential Bull Buyers Perceive Increased Value to their Operations When Purchasing Bulls from the Florida Bull Test - Vitor R. G. Mercadante; Darren D. Henry; Francine M. Ciriaco; Paula M. Mercadante; Tessa Schulmeister; Nicolas DiLorenzo; G. Cliff Lamb (EDIS)
Since its beginning in 2000, the Florida Bull Test has been under constant evolution to achieve its goal of helping producers select high-quality sires, thereby improving production and profitability of beef cattle producers in Florida and the Southeast United States. A survey of potential buyers before the 2014 sale succeeded in identifying which characteristics of bulls are most important to buyers purchasing bulls: purchasing bulls from the Florida Bull Test increases the value of calves sired by improving performance, genetics, and feed efficiency of their herds. This 3-page fact sheet was written by Vitor R. G. Mercadante, Darren D. Henry, Francine M. Ciriaco, Paula M. Mercadante, Tessa Schulmeister, Nicolas DiLorenzo, and G. Cliff Lamb, and published by the UF Department of Animal Sciences, November 2014.